2017
DOI: 10.1080/00071668.2017.1365354
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of chicken stem cell culture methods

Abstract: 1. The avian embryo is an excellent model for studying embryology and the production of pharmaceutical proteins in transgenic chickens. Furthermore, chicken stem cells have the potential for proliferation and differentiation and emerged as an attractive tool for various cell-based technologies. 2. The objective of these studies is the derivation and culture of these stem cells is the production of transgenic birds for recombinant biomaterials and vaccine manufacture, drug and cytotoxicity testing, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Next, we used MEF instead of CEF for EGC derivation in N2B27/R2i + LIF medium. Along with previous studies, [29][30][31] we observed that while MEF played a positive role in derivation of ESCs from blastodermal cells, it was not beneficial for the culture of EGCs. CEF was one of the best substrates that could be used for chicken EGC expansion and proliferation of PGCs.…”
Section: The Influence Of N2b27/r2i + Lif On Chicken Egcs Derivation From Embryonic Gonadal Tissuessupporting
confidence: 81%
“…Next, we used MEF instead of CEF for EGC derivation in N2B27/R2i + LIF medium. Along with previous studies, [29][30][31] we observed that while MEF played a positive role in derivation of ESCs from blastodermal cells, it was not beneficial for the culture of EGCs. CEF was one of the best substrates that could be used for chicken EGC expansion and proliferation of PGCs.…”
Section: The Influence Of N2b27/r2i + Lif On Chicken Egcs Derivation From Embryonic Gonadal Tissuessupporting
confidence: 81%
“…Further studies of gelatin fiber aggregation are warranted, given prior successes using aggregates for high-yield suspension culture of adherent cells. 6,3941 These include scalable systems with serum-free defined media for embryonic stem cell expansion in aggregate, 39 pluripotent stem cell expansion in spinner flasks with differentiation to >90% cardiomyocyte purity, 40 suspension culture of chicken stem cells, 6 as well as strategies that increase adherent single-cell survival efficiency, growth rates, and yield. 41 In our work, the main fiber properties that promoted aggregation were as follows: (i) they resisted degradation in culture for sufficient periods to support cell adhesion and aggregation (~3–14 days) and (ii) fiber length was small compared with aggregate diameter (~50–200 μm).…”
Section: Discussionmentioning
confidence: 99%
“…This is important, because meat consists of muscle, fat, and connective tissues proportioned according to tissue source, 4 each containing a diverse array of nutrients produced by constituent cells. Cell types composing meat can be cultured in vitro 5,6 but production scale-up is limited by the anchorage dependence of these cells, which require attachment to culture substrates for survival, proliferation, and maturation. 7 This requirement is especially stringent for muscle maturation, where alignment of densely packed muscle fibers is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, chicken stem cells have given a perfect opportunity for producing cell-based transgenic birds and a powerful source of cells for vaccine production for poultry and human viral diseases. Besides, they give knowledge into fundamental science namely drug sensitivity testing, cell tracking and cytotoxicity testing [1]. However, various important virus or viral diseases have never been explored at a cellular level so that cell culture technology is still in an early stage of its potential progress.…”
Section: Introductionmentioning
confidence: 99%